2009
DOI: 10.1007/s00253-009-2168-4
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination in the antibiotic producer Penicillium chrysogenum: strain ΔPcku70 shows up-regulation of genes from the HOG pathway

Abstract: In Penicillium chrysogenum, the industrial producer of the beta-lactam antibiotic penicillin, generating gene replacements for functional analyses is very inefficient. Here, we constructed a recipient strain that allows efficient disruption of any target gene via homologous recombination. Following isolation of the Pcku70 (syn. hdfA) gene encoding a conserved eukaryotic DNA-binding protein involved in non-homologous end joining (NHEJ), a Pcku70 knockout strain was constructed using a novel nourseothricin-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 74 publications
2
75
0
Order By: Relevance
“…P. chrysogenum producer strains are known to contain 6 to 14 copies of the clustered penicillin biosynthesis genes (Fierro et al, 2006). We have recently demonstrated that DPcku70 strains can be used to delete single gene copies from the penicillin cluster; however, a simultaneous deletion of all amplified gene copies was impossible (Hoff et al, 2009). Using an alternative RNAi approach, Ullán et al (2008) demonstrated recently the successful expressional downregulation of the multi-copy penicillin biosynthesis genes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…P. chrysogenum producer strains are known to contain 6 to 14 copies of the clustered penicillin biosynthesis genes (Fierro et al, 2006). We have recently demonstrated that DPcku70 strains can be used to delete single gene copies from the penicillin cluster; however, a simultaneous deletion of all amplified gene copies was impossible (Hoff et al, 2009). Using an alternative RNAi approach, Ullán et al (2008) demonstrated recently the successful expressional downregulation of the multi-copy penicillin biosynthesis genes.…”
Section: Discussionmentioning
confidence: 99%
“…This plasmid served as template to generate a 3.8 kb PCR fragment to construct a DPclaeA knockout strain. Plasmid pKOPcVELA_Nat is a derivative of pKOPcVELA in which the phleomycin-resistance gene has been substituted by the nourseothricin-resistance cassette (Hoff et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations